Effect of Attitude on Mobile Banking Acceptance Using Extended UTAUT Model - Angelia Angelia; Erwin Setiawan Panjaitan; Roni Yunis (Institute of Computer Science (IOCS), 2021)
This research aims to evaluate the effect of attitude on mobile banking acceptance using the extended UTAUT Model. Specifically, surveying the Medan city area covered 392 mobile banking users from several banks. By using Structural Equation Modeling (SEM) and SmartPLS software. This research’s man contribution is introducing attitude variables in the combination of UTAUT models, task technology fit, and trust, which have a significant effect on behavior intention. Based on this study results, it shows that social influence and attitude are a significant effect on behavior intention,facilitating condition, and behavior intention is a significant effect use behavior of mobile banking users from several banks. While performance expectancy, effort expectancy, task technology fit, and trust didn’t significantly effect on the behavior intention of mobile banking users from several banks. This Research implies two important policymakers’ findings. First, Banking Management needs to ensure that it always makes necessary improvements in simplifying technology to understand it easily. Second, need to ensure that we regularly evaluate the performance of mobile banking users from several banks to mae benefits of using M-Banking technology to support financial transactions needs.